2013
DOI: 10.1016/j.jagp.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

“Thinking About It for Somebody Else”: Alzheimer's Disease Research and Proxy Decision Makers' Translation of Ethical Principles Into Practice

Abstract: Objectives Ethical guidelines suggest that, when enrolling dementia patients in research, alterative decisionmakers (proxies) should base their decision on a “substituted judgment” of how the patient would have decided. If unable to make a substituted judgment, proxies are asked to decide based on the patient’s best interests. This mixed-methods study is the first to examine explicitly whether and to what degree proxies differentiate between these two approaches, and what considerations influence their mode of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 19 publications
(16 reference statements)
0
33
0
2
Order By: Relevance
“…To guide surrogate decision makers, there is a commonly accepted hierarchy of standards for proxy decisions: (a) explicitly stated wishes of the person (eg, advance directives); if wishes are unknown, then (b) substituted judgment (eg, what the person would have chosen if capable based on the person's values, beliefs, and past decisions); if the surrogate is not able to make a substituted judgment as preferences are unknown, then (c) best interests (eg, what appears to maximize benefit for the person) . When confronted with decisions for a person with dementia such as stopping driving, moving into long‐term care, and end‐of‐life care, it appears that surrogate decision makers aim to strike a balance between respecting the perceived wishes of the person with dementia (eg, substituted judgment) and providing for the best interests of the person given the current state of disease progression .…”
Section: Decision‐making In Clinical Trials For Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…To guide surrogate decision makers, there is a commonly accepted hierarchy of standards for proxy decisions: (a) explicitly stated wishes of the person (eg, advance directives); if wishes are unknown, then (b) substituted judgment (eg, what the person would have chosen if capable based on the person's values, beliefs, and past decisions); if the surrogate is not able to make a substituted judgment as preferences are unknown, then (c) best interests (eg, what appears to maximize benefit for the person) . When confronted with decisions for a person with dementia such as stopping driving, moving into long‐term care, and end‐of‐life care, it appears that surrogate decision makers aim to strike a balance between respecting the perceived wishes of the person with dementia (eg, substituted judgment) and providing for the best interests of the person given the current state of disease progression .…”
Section: Decision‐making In Clinical Trials For Alzheimer's Diseasementioning
confidence: 99%
“…In focusing more on the decision to enroll in clinical trials for Alzheimer's disease, it appears that there is similarly a complex interplay between substituted judgment and best interests standards . For example in a study of one treatment trial, the majority of surrogate decision makers (82% of respondents) reported using the stated preferences of the person with dementia or a substituted judgment standard in making the decision to enroll, whereas other studies showed surrogate decision makers primarily using a best interests standard or some combination of best interests and substituted judgment standards in deciding to enroll a person with dementia in a research trial .…”
Section: Decision‐making In Clinical Trials For Alzheimer's Diseasementioning
confidence: 99%
“…Ethical guidelines and policy rules direct surrogate decision‐makers to look first to the substituted judgment standard, which seeks to replicate the choice the patient would make if he or she were capable of choosing. But empirical studies of dementia research show that surrogates focus as much or more on protecting the patient’s current well‐being (the best‐interest standard) . Many surrogates also say that they rely heavily on the patient’s current preferences, as opposed to past preferences, to guide research decision‐making .…”
Section: The Teachings Of Personal Experiencementioning
confidence: 99%
“…In another study of surrogate decision making for AD research, Overton and colleagues [29] and Dunn and colleagues [30] interviewed a total of 65 surrogate decision makers (primarily spouses and adult children) for people with AD. Each surrogate was randomly assigned to one of four hypothetical clinical trials for a fictional investigational drug for AD created by crossing two levels of risk and two levels of potential benefit.…”
Section: Studies Of Surrogate Decision Making In Ad Researchmentioning
confidence: 99%